Peningkatan Efisiensi Biaya Melalui Integrasi Cabang - Cabang Usahatani Di Nagori Bosar Kecamatan Panombeian Panei - Jhonson A Marbun; Romauli Simanjuntak; Josua Tambunan; Sri Maya Purba; Freddy Pasaribu (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
Nagori Negeri Bosar is an agricultural village located around the oil palm plantation of Marjandi plantation. In general, farmers in this village manage dry land with various types of crops, such as corn, peanuts, cassava, and cocoa. In addition, they also raise livestock, pigs in cages or cattle grazing in plantation areas. The management of farming branches is separate from each other, therefore they are not complementary. This is a problem that is trying to be solved through this community service activity. The purpose of this activity is to integrate farming branches managed by farming families so that efficiency occurs through reducing production costs and will further increase family income as well as the welfare of farmer families This community service activity is intended to empower farmers, especially through a group approach. Various extension methods were applied, such as lectures, field meetings and the practice of processing farm waste into the next production material/input. The results obtained were fodder silage made from corn straw, peanuts and lamtoro leaves and cow dung compost enriched with cocoa husk and oil palm flower buds. The practice of making silage and compost has worked quite well, but the enthusiasm of farmers is still not good, therefore farmer empowerment programs need to be continued by prioritizing changes in mindset or principles of environmentally friendly and efficient farming management